2022
DOI: 10.1002/hyp.14727
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of runoff increase and sea level rise on the water exchange and saltwater intrusion for an estuary bay in non‐flood season

Abstract: Estuary bays are vulnerable to salinization effects due to relative sea level rise and modification in upland hydrology owing to a variety of factors. Much research has evaluated the one‐sided effect of runoff discharge or sea level on the water exchange and saltwater intrusion for an estuary, while their combined effects have not been evaluated, especially for an estuary bay with narrow river mouth. Taking the Wanquan Estuary Bay (WEB), China, as study case, this paper has revealed the long‐term significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that hydrological drought and saltwater intrusion in coastal areas are usually interdependent and that human activities, such as irrigation in coastal areas, reservoir regulation, and water transfer projects, directly influence the evolution of hydrological drought by altering the hydrological processes in the basin, which in turn may affect the evolution of compound drought‐saltwater intrusion (Wu et al, 2022). In this study, we focus only on runoff (SRI) and saltwater intrusion (SSI) because hydrological drought and saltwater intrusion are closely related to water supply in estuary (He et al, 2022; Wei et al, 2022). To address this limitation, more factors (e.g., precipitation, temperature, wind, tide, runoff and saltwater) should be included to complement the framework in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that hydrological drought and saltwater intrusion in coastal areas are usually interdependent and that human activities, such as irrigation in coastal areas, reservoir regulation, and water transfer projects, directly influence the evolution of hydrological drought by altering the hydrological processes in the basin, which in turn may affect the evolution of compound drought‐saltwater intrusion (Wu et al, 2022). In this study, we focus only on runoff (SRI) and saltwater intrusion (SSI) because hydrological drought and saltwater intrusion are closely related to water supply in estuary (He et al, 2022; Wei et al, 2022). To address this limitation, more factors (e.g., precipitation, temperature, wind, tide, runoff and saltwater) should be included to complement the framework in future studies.…”
Section: Discussionmentioning
confidence: 99%